2019
DOI: 10.1590/0103-8478cr20180797
|View full text |Cite
|
Sign up to set email alerts
|

Application of active films with natural extract for beef hamburger preservation

Abstract: Edible chitosan-based films, in pure form (CH100), or blended with gelatin (GEL50:CH50), with and without boldo extract (B) were prepared. The oxygen permeability of the films, as well as color changes and antioxidant and antimicrobial activities on beef hamburgers samples were evaluated. CH100+B film exhibited optimal oxygen barrier properties (6.40±0.170cc-mL/[m²-day]), and this value was significantly increased in blended films (GEL50:CH50+B = 12.99±1.50cc-mL/[m²-day]) (P<0.05). All films provoked color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…There are reported cases where an antimicrobial agent is added to the gelatin film to extend the useful life of the beef meat from eight to 14 days (with respect to the microbial contamination and taking into consideration that it does not refer to ground meat, but to slices of meat) [81]. However, there are authors, like Bonilla Lagos et al [82], who have studied samples with an initial contamination higher than 1000 CFU/g and after seven days some samples protected with film incorporating natural extracts reached levels between 5 and 7 (Log of CFU/g sample). However, it can be said that the films did not give significant protection against microbial contamination.…”
Section: Film Protection In Beef Pattiesmentioning
confidence: 99%
“…There are reported cases where an antimicrobial agent is added to the gelatin film to extend the useful life of the beef meat from eight to 14 days (with respect to the microbial contamination and taking into consideration that it does not refer to ground meat, but to slices of meat) [81]. However, there are authors, like Bonilla Lagos et al [82], who have studied samples with an initial contamination higher than 1000 CFU/g and after seven days some samples protected with film incorporating natural extracts reached levels between 5 and 7 (Log of CFU/g sample). However, it can be said that the films did not give significant protection against microbial contamination.…”
Section: Film Protection In Beef Pattiesmentioning
confidence: 99%
“…(2022) found that the luminosity in samples of beef steaks coated with chitosan or chitosan/lauric acid remained constant compared to the uncoated sample during 21 days of storage. However, some studies report that there may be a reduction in the brightness of meat when compared to the control depending on the type of polymer used in the coatings (Georgantelis et al ., 2007; Lagos & Sobral, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A novel approach to enhancing the shelf life of food products and their preservation involves the use of active, edible films, which mainly contain antimicrobial agents [1]. Various biopolymers are used in the production of such film.…”
Section: Discussionmentioning
confidence: 99%
“…When stored at the temperature of 4 ºC, the shelf life of fresh beef is extremely low (3-5 days), which is attributed to the high water content and chemical composition of the food. These factors often facilitate hazardous microbial growth, thereby leading to the spoilage of meat [1]. Although preventive measures are observed in animal slaughter and proper hygiene and productive measures are also taken in the other stages of meat processing, pathogenic bacterial contamination remains an important health threat in the case of raw meat and other meat products.…”
Section: Introductionmentioning
confidence: 99%